Answer:
yeah so it is 74882828 it is pretty easy
Answer:
CD= 2x-1
Step-by-step explanation:
AD = 6x-4
AC = 4x - 3
CD= AD- AC
CD= 6x-4 - (4x - 3)
CD= 6x - 4 - 4x +3
CD= 2x -1
Therefore, the value of CD= 2x-1
You haven't shared the possible answers, so the best I can do (which is very good!) is to assume we want to change from base 4 to base 10 and then apply the change of base formula.
Given log-to-the-base-4-of (x+2), we want log-to-the-base-10 of (x+2). Following the change of base formula,
log-to-the-base-4-of (x+2)
log-to-the-base-10 of (x+2) = ------------------------------------
log-to-the-base-4-of-10